2018
DOI: 10.3349/ymj.2018.59.9.1079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidant Tempol on Systematic Inflammation and Endothelial Apoptosis in Emphysematous Rats Exposed to Intermittent Hypoxia

Abstract: PurposeObstructive sleep apnea and chronic obstructive pulmonary disease are independent risk factors of cardiovascular disease (CVD), and their coexistence is known as overlap syndrome (OS). Endothelial dysfunction is the initial stage of CVD; however, underlying mechanisms linking OS and CVD are not well understood. The aim of this study was to explore whether OS can lead to more severe inflammation and endothelial apoptosis by promoting endothelial dysfunction, and to assess the intervention effects of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A previous study reported that circulating endothelial cell apoptosis is an indicator of vascular injury in vitro (Feng et al, 2012), and an increasing number of studies show that chronic IH caused by oxidative stress can induce endothelial cell apoptosis, lead to loss of endothelial integrity, aggravate VE damage, promote the expression of redox-sensitive genes and adhesion molecules, and lead to the progression of hypoxiainduced cardiovascular diseases (Liu et al, 2018;Xiao et al, 2019). Zhao et al (2018) found that IH-and cigarette smokeinduced emphysema can synergistically produce a greater inflammatory response and endothelial cell apoptosis in an animal model of OSAS and chronic obstructive pulmonary disease. They also showed that use of the antioxidant Tempol could antagonize these effects, as the density of apoptotic endothelial cells in OSAS patients was higher than that in non-OSAS patients.…”
Section: Endothelial Apoptosismentioning
confidence: 99%
“…A previous study reported that circulating endothelial cell apoptosis is an indicator of vascular injury in vitro (Feng et al, 2012), and an increasing number of studies show that chronic IH caused by oxidative stress can induce endothelial cell apoptosis, lead to loss of endothelial integrity, aggravate VE damage, promote the expression of redox-sensitive genes and adhesion molecules, and lead to the progression of hypoxiainduced cardiovascular diseases (Liu et al, 2018;Xiao et al, 2019). Zhao et al (2018) found that IH-and cigarette smokeinduced emphysema can synergistically produce a greater inflammatory response and endothelial cell apoptosis in an animal model of OSAS and chronic obstructive pulmonary disease. They also showed that use of the antioxidant Tempol could antagonize these effects, as the density of apoptotic endothelial cells in OSAS patients was higher than that in non-OSAS patients.…”
Section: Endothelial Apoptosismentioning
confidence: 99%